Project Management Office Models - Monteiro, António (2016)
Monteiro, A., Santos, V., & Varajão, J. (2016). Project Management Office Models: A Review. In International Conference on ENTERprise Information Systems/International Conference on Project MANagement/International Conference on Health and Social Care Information Systems and Technologies, CENTERIS/ProjMAN / HCist 2016 (Vol. 100, pp. 1085-1094). (Procedia Computer Science; Vol. 100). https://doi.org/10.1016/j.procs.2016.09.254